2017
DOI: 10.3847/1538-4365/229/1/17
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Magnetic Flux Emergence Rate in the Quiet Sun from Sunrise Data

Abstract: Small-scale internetwork (IN) features are thought to be the major source of fresh magnetic flux in the quiet Sun. During its first science flight in 2009, the balloon-borne observatory Sunrise captured images of the magnetic fields in the quiet Sun at a high spatial resolution. Using these data we measure the rate at which the IN features bring magnetic flux to the solar surface. In a previous paper it was found that the lowest magnetic flux in small-scale features detected using the Sunrise observations is 9… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 60 publications
(100 reference statements)
2
36
2
Order By: Relevance
“…We note further that similar energetic events at the feet of coronal loops could possibly create jet-like structures observed at these locations (Chitta et al 2017a,b). In addition, given the increasing evidence for the presence of unresolved minority polarities in the photosphere (e.g., Solanki et al 2017;Smitha et al 2017), such ejections resulting from flux cancellation can give rise to jet-like features found inside plages and strong network associated with the unresolved underlying minority polarities (Wang 2016;Wang et al 2019). We expect that other small-scale phenomena, such as spicules, could be associated with reconnection at lower atmospheric heights between converging cancelling polarities, and can potentially be associated with the cool outflows predicted from our model for different values of parameter space (e.g., Samanta et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We note further that similar energetic events at the feet of coronal loops could possibly create jet-like structures observed at these locations (Chitta et al 2017a,b). In addition, given the increasing evidence for the presence of unresolved minority polarities in the photosphere (e.g., Solanki et al 2017;Smitha et al 2017), such ejections resulting from flux cancellation can give rise to jet-like features found inside plages and strong network associated with the unresolved underlying minority polarities (Wang 2016;Wang et al 2019). We expect that other small-scale phenomena, such as spicules, could be associated with reconnection at lower atmospheric heights between converging cancelling polarities, and can potentially be associated with the cool outflows predicted from our model for different values of parameter space (e.g., Samanta et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the Imaging Magnetograph eXperiment (IMaX) instrument on two flights of the SUNRISE balloon Mission (Solanki et al 2010 has revealed glimpses of the photospheric magnetic field at much higher spatial resolution than before, namely, 0.15 arcsec, a factor of six better than the Helioseismic and Magnetic Imager (HMI) instrument on the Solar Dynamics Observatory (SDO; Pesnell et al 2012). Using the observations from the first flight of SUNRISE, Smitha et al (2017) tracked magnetic features with fluxes of 10 15 -10 18 Mx in the Quiet Sun and found a flux emergence and cancellation rate of 1100 Mx cm −2 day −1 . This rate is an order of magnitude higher than previous measurements.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, the quiet Sun is where the Sun exhibits minimal solar activity, and no large-scale magnetic flux emergence occurs. On the other hand, new magnetic flux does appear in the interior of supergranular cells (see Thornton & Parnell 2011;Gošić et al 2016;Smitha et al 2017, and references therein); Smitha et al (2017) found the flux emergence rate of 1100 Mx cm −2 day −1 . Moreover, with time, a significant fraction of newly appeared magnetic elements dissipate by cancellation with opposite polarity patches (Gošić et al 2016;Smitha et al 2017).…”
Section: Discussionmentioning
confidence: 99%